Assessment about Awareness of Tuberculosis in TB Patients as Well as General Population - Kallol Mallick; Rachna Prasad; Rajiv kumar Prasad; Anamika K Majumdar (Medsci Publications, 2019)
Introduction: India, the home of 1/5 global burden of Tb, needs its awareness in patients as well as general population for early diagnosis and adequate treatment. Reasons for delay in diagnosis may be clinical presentation, host response chemotherapeutic response; social implications etc. Implications of delay are associated with increased transmission, morbidity and mortality 1. For this we have conducted an awareness campaign on the eve of World Tb day to generate as well as estimate the knowledge about Tb in urban areas slum / construction sites. Main emphasis was given on TB as disease, its prevention and control and availability of its treatment free of cost. Results: totally 22 Tb patients were interviewed,4 (18.18%) were in MDR/XDR category, 16 (72.7%) were in Cat I and 2 (9%) were in Cat II. Nine (40.9%) patients were between 20-40 yrs, 9(40.9%) were between 40-60 yrs, 3 (1.36%) were below 20 yrs and 1 (4.5%) was above 60 yrs. Maximum of tuberculosis patients were either illiterate or primary school passed. Discussion: Smear positivity was highest (40.9 %) in 20-60 years age group and least in below 20 years (1.36%). Male, female ratio was 6:4. Conclusion: Health workers coverage, patient's care including compliance and their rapport in the society was found to be excellent.